Assessment and Comparative Evaluation of Self-Efficacy as a Function of Training Style. Issue 1 (September 2020) - Bliss, James P.; Hartzler, Beth M.; Winner, Jennifer; Hodge, Douglas
As with civilian medicine, the Military Health System relies on medical manikins to supplement didactic training. Analyses of transfer-of-training and the calibration between self-efficacy (SE) and competence offer a robust look at training effectiveness; however, the logistics of collecting these data are complex. Self-reported SE is commonly used as a starting point to look at training effectiveness, and prior research has used it to compare didactic against simulation-based training options. Military medical training courses, however, often combine didactic and experiential (simulation-based) training. Little or no work has documented how SE is differentially affected in courses using both training approaches. Results reported here represent SE data from enlisted medical technicians completing pre-deployment readiness training. These data illustrate that SE gained through didactic training was maintained throughout the simulation training. We discuss possible reasons why this sample did not demonstrate further significant gains following simulation and we identify challenges associated with the study of individual constructs such as SE in the context of team-based training environments.